Maternal health care access among migrant women labourers in the selected brick kilns of district Faridabad, Haryana: mixed method study on equity and access - Archana Siddaiah; Shashi Kant; Partha Haldar; Sanjay K. Rai; Puneet Misra (International Journal for Equity in Health, 2018)
Abstract Background Socio-economic inequity leads to health inequity. Inequity is closely intertwined with internal migration. This study was planned with the objective of documenting the maternal health care utilization among women labourers working in brick kilns situated in an area of Haryana, north India. Methods A community based mixed method study was done in select brick kilns of Faridabad district in north India. A mixed method study was done to assess maternal health care utilization in a sample of 500 women in the reproductive age group. Focus group discussions were also carried out. Descriptive analysis was done. Qualitative data was analysed using the thematic framework approach. Results The mean age of the women was 30 (SD 0.3) years. Mean number of pregnancies per woman was 3.1 (SD 1.7). Only 22.9% ever had institutional delivery. About one third of women had ever received cash benefit under Janani SurakshaYojana (JSY) or had ever used free ambulance services. Seven major themes emerged from the qualitative analysis. Important themes include-Gaps in knowledge regarding local health system; Sub-standard private health care delivered at brick kilns prevent migrants from accessing the basic public health services; Misconceptions and mistrust about public health system influenced maternal health care utilization; Barriers to avail universal health coverage: location of brick kilns, time, apathy of public health system, partial health insurance cover. Conclusions A typical migrant woman labourer in the brick kiln was an illiterate, had migrated from poor states, belonged to a socially disadvantaged community and worked long hours, and had been doing so for many years. This study has identified migrant women working in brick kilns as a vulnerable population subgroup in terms of maternal health utilization. To achieve universal health care it is important to understand the needs of all population subgroups and make concerted efforts at the health system level.